Pentingnya Media Promosi dalam Pemasaran : Lokakarya Pengembangan Media Sosial bagi Pemasaran Pariwisata di Desa Kertarahayu - Nurfadilla, Ariska ariska (Rumah Jurnal UNEJ, 2022)
Kertarahayu Village, Setu , Bekasi Regency is one of the villages that has regional potential in the Creative Economy (Tourism and UMKM) sector. The variety of tourist attractions that have the potential to be owned by Kertarahayu Village. However, the tourism sector has not become a local or national tourist attraction due to the lack of dissemination of information or promotion, especially on social media. By looking at the opportunities and potentials of resources both natural and man-made, if managed and developed and marketed properly, especially with technological advances and marketing 4.0, it can have a good impac on the economoy and existence of Kertarahayu Village. Marketing is the most important yhing in running a business from the small sector, marketing is the most major thing, with such a background.